THE DEAD TEACHING THE LIVING – BODY WORLDS - Magda Slabbert; Bonnie Venter (Obiter, 2014)
The Body Worlds exhibition takes the visitor through a journey of more than 200 specimens. These various skinless full body plastinates are posed in different positions to display how the human body works; they vary from the chess player with his brain split open to display the brain “in action”, the runner with his muscles falling off the bones to display the working of the muscles in athletics and the controversial pregnant woman with her womb cut open to show her eight month old foetus. Von Hagens the creator of Body Worlds believes his exhibition is educational – educating the masses. Since the first exhibition of Body Worlds there has been rigorous debate on whether the display is a violation of human dignity or not. This aspect is discussed in the article. In conclusion the process regarding donating a complete dead body in South Africa is highlighted and the question is answered whether a South African citizen could legally donate his or her body to a Body Worlds display.